Changes in Testosterone Levels Following Surgical Sperm Retrieval in Men with Non-Obstructive Azoospermia: Systematic Review and Meta-Analysis - Wael Zohdy; Rupin Shah; Christopher Chee Kong Ho; Gokhan Calik; Vineet Malhotra; Bircan Kolbaşı Erkan; Mesut Berkan Duran; Georgios Tsampoukas; Garaz Radion; Ramadan Saleh; Ahmed M. Harraz; Parviz Kavoussi; et al. (The World Journal of Men's Health)
Purpose: Surgical sperm retrieval (SSR) is used to extract spermatozoa for use with intracytoplasmic sperm injection in men with obstructive and non-obstructive azoospermia (NOA). The procedure may lead to segmental devascularization, postoperative fibrosis, and atrophy with a subsequent decrease in testosterone. The aim of the study is to investigate the impact of SSR on serum levels of total testosterone (TT), follicle-stimulating hormone (FSH), luteinizing hormone (LH) testicular volume, and sexual function in infertile azoospermic men. Materials and Methods: In this systematic review and meta-analysis (SRMA), we searched articles in “PubMed” and “Scopus” exploring the impact of SSR on TT, FSH, LH, and testicular volume. The full-text articles were screened to assess eligibility before data extraction, quality assessment, and meta-analysis. Results: Seventeen studies meeting the inclusion criteria were finally analyzed and included 1,685 infertile, azoospermic men. Patients underwent SSR and were followed in the postoperative period (one week to 32 months). The analysis showed a significant reduction in TT (mean difference [MD] 3.81 nmol/L, 95% confidence interval [CI] 0.55:7.06; p=0.02) compared to pre-SSR values. We also observed insignificant differences in serum FSH (MD 5.08 IU/L, 95% CI -5.6:15.8; p=0.35), LH (MD -2.96 IU/L, 95% CI -6.31:0.39; p=0.08), and no change in testicular volume (MD 0.07 mL, 95% CI -1.92:2.07; p=0.94) after SSR. Sexual dysfunction was associated with hypogonadism, depression, and anxiety, especially in men with unsuccessful SSR and Klinefelter syndrome. Conclusions: The results of this SRMA indicate a significant reduction in TT after SSR. Sexual dysfunction after testicular sperm extraction and the potential negative impact of future SSR repeat should be considered during preoperative counseling.